Effect of Supplementing Syzygium Cumini (Jamun) Fruit to Total Mixed Ration on the Performance of Lactating Cross Bred Cows - Mayuresh, A H; Wadhwa, M; Hundal, J S; Bakshi, M P S; Sharma, Amit; Kaur, Simerjeet; Bansal, B K (Indian Journal of Animal Nutrition, 2020)
This study was taken up to assess the effect of supplementing Syzygium cumini (Jamun) fruit shreds on nutrient utilization, enteric methane emission and performance of the lactating crossbred cows. Â Twelve lactating crossbred cows (CBCs) divided into two equal groups were fed a total mixed ration (TMR) containing concentrate mixture, Trifolium alexandrium (Berseem) green fodder and wheat straw in 40: 42: 18 ratio on DM basis supplemented with or without S. cumini @ 2% for 180 days. A 14-day digestion trial was conducted by indicator method using chromic oxide green as an external marker, before the termination of feeding trial,. The enteric methane production was assessed by SF6 tracer technique. The data were analyzed by one way ANOVA and factorial design. S. Cumini fruit shreds are rich source of phenolics (21.78%), antioxidants (4.95%) and saponins (4.35%). Supplementation of diet with S. cumini fruit shreds did not affect DM intake and digestibility of nutrients. The methane emission was mitigated (p